Applying Mindfulness Techniques to the Management of Depressive Tendencies in Women in Taiwan in the Perinatal Period: A Qualitative Study - Wan-Lin Pan; Meei-Ling Gau; Tzu-Chuan Hsu; Shu-Chiao Shen; Tzu-Ying Lee (Elsevier, 2022)
Summary: Purpose: Perinatal distress, especially depression, commonly occurs during pregnancy and the first year postpartum, but this medical condition are often undiagnosed and untreated. The present study explored how women with depressive symptoms during the perinatal period who had participated in a mindfulness course applied the training and perceived its effects. Methods: This descriptive qualitative study included 16 women with probable perinatal depression who had participated in an 8-week mindfulness-based childbirth and parenting program during their pregnancy and agreed to be interviewed. One-to-one in-depth interviews were conducted and recorded following the completion of the mindfulness course, approximately 1 month after childbirth. Verbatim transcripts were analyzed using content analysis. Results: We proposed three themes and six subthemes relating to first-time mothers' experiences during and after the group mindfulness-based intervention: learning to be aware of the body and mind (confronting awareness of physical change, managing negative feelings differently), building positive family relationships (strengthening the mother-baby bond, developing a satisfactory marital partnership), and overcoming ongoing challenges (conquering childbirth pain with confidence, accepting unexpected situations). Three main themes were generated to demonstrate how women experience the effects of mindfulness training. Conclusions: Mindfulness-based interventions helped the participants develop insight into their mood and physical changes and accept their childbirth process. Therefore, mindfulness education programs can be incorporated into prenatal care to enhance the management of the depressive symptoms of perinatal women.